100 Years of Conference Interpreting A Legacy (Cambridge Scholars Publishing, 2021)
When Woodrow Wilson, David Lloyd George, Vittorio Emanuele Orlando and Georges Clemenceau met in Versailles in January 1919, they ushered in the modern era of multilateral diplomacy and--perhaps inadvertently--laid the foundation for a new profession. Indeed, communication among these statesmen was only possible thanks to the first conference interpreters. For the following 100 years, these interpreters would become a permanent fixture at all international multilateral conferences. As we celebrate one century of conference interpreting, this volume takes stock of some of the most important mil.